2023
DOI: 10.1029/2022gl102678
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Shallow Slow Earthquakes by Distributed Acoustic Sensing Using Offshore Fiber‐Optic Cable in the Nankai Trough, Southwest Japan

Abstract: Off Cape Muroto area, along the Nankai Trough in southwest Japan, is a typical area with adjacent occurrences of slow and megathrust earthquakes. High‐resolution monitoring of slow earthquakes is necessary to understand tectonic conditions. In the off Muroto area, distributed acoustic sensing (DAS) measurement, which provides high‐density strain data, has been conducted using offshore fiber‐optic cable. We observed shallow tremors, a type of slow earthquakes, using DAS measurement for the first time. The chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Seismic observations based on distributed acoustic sensing (DAS) can solve these issues. DAS is a recently developed method of measuring dynamic strain along a ber-optic cable and has been applied to seismic observations in which sea oor ber-optic cables are used to simulate arrays of seismometers (e.g., Lindsey et (Baba et al 2023) has demonstrated the capability to observe a wide range of seismic signals. Because DAS equipment can be installed at the landing stations of ber optic cables, ocean-oor seismic motions can be recorded in real time with installation and maintenance costs far lower than those of ocean-bottom seismometers or seismic stations on remote islands.…”
Section: Detailed Analyses Bymentioning
confidence: 99%
“…Seismic observations based on distributed acoustic sensing (DAS) can solve these issues. DAS is a recently developed method of measuring dynamic strain along a ber-optic cable and has been applied to seismic observations in which sea oor ber-optic cables are used to simulate arrays of seismometers (e.g., Lindsey et (Baba et al 2023) has demonstrated the capability to observe a wide range of seismic signals. Because DAS equipment can be installed at the landing stations of ber optic cables, ocean-oor seismic motions can be recorded in real time with installation and maintenance costs far lower than those of ocean-bottom seismometers or seismic stations on remote islands.…”
Section: Detailed Analyses Bymentioning
confidence: 99%
“…Very low frequency earthquakes (VLFE) and tremors, which are types of seismic slow earthquakes, have been detected in the shallow megathrust of the Nankai Trough (<30 km) and show a clustered distribution (Figure 1) (Nakano et al., 2018; Ogiso & Tamaribuchi, 2022; Takemura, Matsuzawa, et al., 2019; Takemura, Noda, et al., 2019; Takemura, Baba, et al., 2022; Takemura, Obara, et al., 2022; Tamaribuchi et al., 2022). Previous studies have suggested possible factors affecting the spatial distribution of VLFEs and tremors such as the presence of a subducted seamount (Baba et al., 2023; Sun et al., 2020; Takemura, Matsuzawa, et al., 2019), pore fluid pressure (Hirose et al., 2021; Kitajima & Saffer, 2012; Kodaira et al., 2004), sediment thickness and lithology (Ike et al., 2008; Park and Jamali‐Hondori, 2023; Tilley et al., 2021) and slip‐deficit rate (Yokota et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With a high density of channels along the cable, the distributed acoustic sensing (DAS) technique can monitor the horizontal component of strain along the cable direction, which allows us to investigate the spatial variation of wavefields in detail, including on seafloor telecom cables (Lindsey et al., 2019; Sladen et al., 2019; Williams et al., 2019). This technique has been widely used in marine geophysics for sensing distances of 50–120 km from coastlines to investigate seismological subseafloor structures (Cheng et al., 2021; Fukushima et al., 2022; Lior et al., 2022; Spica et al., 2020; Tonegawa et al., 2022; Viens et al., 2022, 2023), hydroacoustic waves (Matsumoto et al., 2021), Scholte wave generation (Spica et al., 2022), ocean surface gravity waves (Williams et al., 2019), and shallow slow earthquakes (Baba et al., 2023). Ocean DAS records were also uploaded to a repository (Spica et al., 2023) as part of a project that collected DAS data for teleseismic events that occurred in February 2023 (Wuestefeld & Wilks, 2019).…”
Section: Introductionmentioning
confidence: 99%